Information feedback and bidders' competitiveness in construction bidding. Issue 5 (9th September 2014) - Lan Oo, Bee; Yean Yng Ling, Florence; Soo, Alexander
Abstract : Purpose: – Contractors rely on effective pricing methods in order to translate potential business into reality for long-term survival of their firms. This involves effective utilization of bidding feedback information toward winning jobs with high profit potential. The purpose of this paper is to experimentally investigate student (inexperienced) bidders' competitiveness under full and partial information feedback conditions when the number of competing bidders is large ( n =12). Design/methodology/approach: – This paper adopted an experimental research design. The design used between-subjects variation and involved information feedback as the treatment variable with 120 students who enrolled in a cost-estimating course participated in the experiment. Findings: – The result shows that the variations in bids over time for both levels of information feedback are statistically significant. It is found that bidders with full bidding feedback information are more competitive than those with partial bidding feedback information. The bid-spread analysis and the identified effect of these two information feedback conditions on awarded contract sum, provide some further evidence that full information feedback condition would lead to lower average bids in construction bidding. Practical implications: – The implication of the findings for construction clients is that they should provide as much bidding feedback information as possible so that the bid prices will be competitive. Originality/value: – Given the ambiguity inherent in field data, this paper provides strong justification of using experimental research design in advancing the understanding of construction pricing under different information feedback conditions. In addition, it demonstrated the suitability of using student subjects in similar experiments in the context of construction bidding.